A randomized controlled trial of preemptive rituximab to prevent recurrent focal segmental glomerulosclerosis post-kidney transplant (PRI-VENT FSGS): protocol and study design - Rheault, Michelle N.; Amaral, Sandra; Bock, Margret; Chambers, Eileen Tsai; Chavers, Blanche; Ters, Mireile El; Garro, Rouba; Gbadegesin, Rasheed; Govil, Amit; Harshman, Lyndsay; Amer, Hatem; Hooper, David K.; et al. (Frontiers in Nephrology, 2023)
Background: Focal segmental glomerulosclerosis (FSGS) is a common cause of end-stage kidney disease requiring kidney transplantation and can recur in the allograft in 30-80% of recipients resulting in reduced graft survival. Plasmapheresis has shown efficacy in treating some cases of recurrent FSGS but isolated plasmapheresis has not demonstrated efficacy in preventing recurrent FSGS. Rituximab has had anecdotal success in preventing recurrence in a single center study but has not been studied in combination with plasmapheresis for preventing FSGS recurrence. Methods: We are conducting a randomized, controlled, multicenter clinical trial of adult and pediatric kidney transplant recipients with primary FSGS to assess whether plasmapheresis in combination with rituximab prevents recurrent disease post-transplantation. Discussion: Rituximab combined with plasmapheresis is a promising, novel therapy to prevent recurrent FSGS, a disease with limited therapeutic options and no consensus guidelines for prevention or treatment. Trial Registration: Clinicaltrials.gov, NCT03763643. Registered on December 4, 2018 https://clinicaltrials.gov/ct2/show/NCT03763643